PENERAPAN MODEL GROUPING INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA UMMY SOLOK DALAM MATA KULIAH EVALUASI PEMBELAJARAN MATEMATIKA (Universitas PGRI Sumatera Barat, 2011)
The capability of thinking critically of the students of UMMY Solok is still low on the subjectEvaluasi Pembelajaran Matematika. From the previous research on this matter, the students tended tobe passive on the process of learning in class, as the impact most of the students was still not able incollecting, analyzing, synthesizing the objects of the lesson, drawing conclusion from the object of thelesson, assessing and correcting the objects of the lesson with the right argumentation, and to solvethe problem on the objects of the lesson. This research is aimed at improving the capability of thestudents through the learning cooperatively with the model of Grouping Investment. Identification ofthe problem in this research is can the model of learning Grouping Investigation improve the skill ofthinking critically of the students of UMMY Solok seen from the indicator of capability of collecting,analyzing, synthesizing the objects of the lesson, capability of drawing the conclusion of the object ofthe lesson, correcting and assessing the objects of the lesson, and the capability of solving the problemon the objects of the lesson.This research is the mixing of the action research and class action research. Before conductingthe class action research, the researcher doing some actions. The action research is integrated whollyto the class action research, so that this step is believed as a continuity process. The subject of thisresearch is the students of fifth semester with the total of 35 students. The data is collected throughobservation sheet, problem design, field notes, and interview. The data is analyzed by simplepercentage and described by descriptive analysis.The results of the research show that the learning using the model of Grouping Investigationcan improve the skill of thinking critically of the students on the subject Evaluasi PembelajaranMatematika. The improvement is shown by 100% of the students is good at collecting the objects ofthe lesson, 71.43% of the students is good at synthesizing the objects of the lesson, 85.71% of thestudents is good at analysing the objects of the lesson, 83,71% of the students is good at drawing theconclusion of the objects of the lesson, 83.33% of the students is good at correcting the objects of thelesson, and 74.19% of the students is good at solving the problem. This shows that the model ofgrouping Grouping Investigation can improve the skill of think critically of the students of UMMYSolok on the subject of Evaluasi Pembelajaran Matematika.